Serum Cystatin C Reflects the Progress of Albuminuria - Jeong Seon Yoo (Diabetes & Metabolism Journal, 2011)
BackgroundResearch on the relationship between urinary albumin excretion and serum cystatin C in diabetes is restricted to cross-sectional studies. In this study, we investigated how well serial measurements of serum cystatin C level reflect changes in the urinary albumin excretion rate.MethodsWe enrolled and retrospectively collected data on 1,058 participants with type 2 diabetes who were older than 18 years and who had more than 3 years of follow-up with serial measurements of albuminuria and serum cystatin C at an outpatient clinic.ResultsWith the use of a linear mixed model, we found that the albuminuria level for each patient over time corresponded with the annual change in serum cystatin C-based estimated glomerular filtration rate (cysC-eGFR) but did not correspond with the creatinine-based eGFR calculated by the modification of diet in renal disease formula (MDRD-eGFR). The discrepancy in the direction of the trend was smaller with cysC-eGFR than with MDRD-eGFR.ConclusionSerum cystatin C level reflects the trend in albuminuria level more accurately than serum creatinine level in Korean type 2 diabetes mellitus patients.